Effects of the cooling rate on the shear behavior of continuous glass fiber/impact polypropylene composites (GF-IPP). (December 2016) - Wafai, H.; Lubineau, G.; Yudhanto, A.; Mulle, M.; Schijve, W.; Verghese, N.
Abstract: Fiber-reinforced composites with improved dissipation of energy during impact loading have recently been developed based on a polypropylene copolymer commonly called impact polypropylene (IPP). Composites made of IPP reinforced with glass fibers (GF) are particularly attractive to the automotive industry due to their low cost and good impact resistance. In such composites, the cooling rate varies depending on processing techniques and manufacturing choices. Here, we study the effects of the cooling rate of GF-IPP composites on shear behavior, which is critical in impact applications, using [ ± 45 ] s monotonic and cyclic (load/unload) tensile specimens. The specimens were manufactured under a wide range of cooling rates (3 °C/min, 22 °C/min, 500–1000 °C/min). Mainly dominated by the properties of the matrix, the global shear behavior of GF-IPP composites differed considerably with respect to the cooling rate. However, the performance of the fiber-matrix interface (chemically modified) appeared to be unaffected by the range of cooling rates used in this study. We found that the cooling rate has a minor effect on the rate of damage accumulation, while it strongly modifies the shear-activated rate-dependant viscoelastic behavior.